Efficient cloning of linear DNA inserts (ECOLI) into plasmids using site-directed mutagenesis - Paclikova, Petra; Harnos, Jakub (Scientific reports, 2024)
This study introduces a novel cost-effective technique for cloning of linear DNA plasmid inserts, aiming to address the associated expenses linked with popular in vitro DNA assembly methods. Specifically, we introduce ECOLI (Efficient Cloning Of Linear Inserts), a method utilizing a PCR product-based site-directed mutagenesis. In comparison to other established in vitro DNA assembly methods, our approach is without the need for costly synthesis or specialized kits for recombination or restriction sites. ECOLI offers a fast, efficient, and economical alternative for cloning inserts up to several hundred nucleotides into plasmid constructs, thus enhancing cloning accessibility and efficiency. This method can enhance molecular biology research, as we briefly demonstrated on the Dishevelled gene from the WNT signaling pathway.
Keywords: Mutagenesis; Mutagenesis, Site-Directed; mutageneze cílená; PCR; DNA; klonování DNA; Plasmids; Site-directed mutagenesis; plazmidy; Cloning, Molecular; polymerázová řetězová reakce; Dishevelled; Polymerase Chain Reaction; DNA cloning; In vitro DNA assembly; Plasmid-based cloning